Imagining a Multilingual Cyberspace - Zaugg, Isabelle (My University, 2019)
This chapter in the book "Finding control: Visions for the Future Internet," addresses steps diverse stakeholders can take to build language equity in cyberspace. It draws on research on grassroots development of digital supports for Ethiopian and Eritrean languages written in the Ethiopic script, as well as the ongoing challenges that constrain the digital vitality of many languages across the globe.
Keywords: digital equity; digital inequality; Ethiopia